Sintak Pedorak: Metode Pengobatan Tradisional Etnis Melayu Rawak Sekadau Kalimantan Barat - Karmila Karmila; Arkanudin Arkanudin; Adi Suryadi; Ignasia Debbye Batuallo (Ideas Publishing, 2023)
The Malay ethnic community of Rawak Sekadau still practices traditional medicine with the Sintak Pedorak method, especially to cure diseases caused by spirits/unseen beings. This study aims to explain the process of traditional medicine carried out with the Sintak Pedorak method. This research uses descriptive qualitative research with data collection techniques using observation, interviews, and documentation. The results of the study found that before the treatment process was carried out, it was preceded by preparing materials that would be given spells with the intention of treating those who recovered. This traditional healing method still exists and is trusted by the Rawak Malay community as a powerful method.